2016
DOI: 10.1021/acs.jced.5b00821
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Inorganic Salts on the Phase Equilibrium of Triton X-114 Aqueous Two-Phase Systems

Abstract: In this work, we studied the liquid–liquid equilibrium of ternary systems containing nonionic surfactant Triton X-114, inorganic salts, and water. The salt impact of five different sodium salts (NaCl, NaBr, NaI, Na2SO4, and Na2HPO4) and four different chlorides (NaCl, KCl, LiCl, NH4Cl) was investigated. The influence of the inorganic additives was studied at 30 °C because at this temperature all prepared mixtures faced a separation above the cloud point temperature (CPT) in micellar (surfactant-rich) and aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 30 publications
3
23
0
Order By: Relevance
“…However, the continuous extraction was performed in presence of a phosphate buffer, which influences the miscibility gap. In a previous study it was shown that phosphate salt increases the miscibility gap, which even enhances the suitability of the system for extraction processes . Nevertheless, due to the small phosphate concentration (100 mM), the impact of the buffer solution on the LLE used in this work is rather small.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…However, the continuous extraction was performed in presence of a phosphate buffer, which influences the miscibility gap. In a previous study it was shown that phosphate salt increases the miscibility gap, which even enhances the suitability of the system for extraction processes . Nevertheless, due to the small phosphate concentration (100 mM), the impact of the buffer solution on the LLE used in this work is rather small.…”
Section: Resultsmentioning
confidence: 90%
“…At 37 °C, which is a tolerable temperature for many biotechnological processes, a density difference of around 0.01 g cm −3 was found. Despite that the density difference might be a limiting parameter in case of other surfactants, the density difference determined at 37 °C in the system with Tergitol NP‐7 was in a range suitable for continuous extraction processes as shown in former studies , .…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Knowledge of the CP helps us to evaluate the storage steadiness since storing formulations at temperatures considerably above the CP causes in phase partition as well as instability. The employment of nonionic surfactants in engineering, as well as pharmaceutical formulation, is remarkable and in the solid medium withdrawal of numerous kinds of diverse organic molecules by means of hydrated phase . Nonionic surfactants also show the best possible efficiency when utilized close or under their CP.…”
Section: Introductionmentioning
confidence: 99%